Symbiotic Characteristics of Azide-resistant Mutants of Moth Bean (Vigna aconitifolia) Rhizobium - Chakraborty, Manigopa; Ramkrishna, K (Annals of Arid Zone, 2016)
Spontaneously arising azide-resistant mutants were isolated from a hypermotile . mutant strain of Rhizobium MR 125 s2-smr 8-hyp5 that nodulates moth bean (I'igna aconitifolia Jacq. Marechal). The mutants generally produced more nodules (30% more) than the parent. One of the mutants MR 125 s2-smr 8-hyp5-azr57 produced 3-fold more nodules than parent. Eleven mutants accumulated signilicantly more nitrogen than the parent in the plants grown in nitrogen-free Amon's nutrient medium. Results indicate that incorporation of azide resistance frequently leads to improved effectiveness.